Supporting student nurses to develop healthy conversation skills. (2nd November 2021) - Mills, Anne; Knight, Anneyce; Burdett, Teresa
Abstract : As advocates for health, nurses are ideally situated to deliver effective health promotion in their daily interactions with people. This work evaluates the integration of healthy conversation training, making every contact count (MECC), into a health promotion module in an undergraduate nursing degree at a higher education institute (HEI). In all, 108 students completed the online questionnaire I year after receiving healthy conversation training. 67% of students reported the regular or occasional use of healthy conversation skills and identified a wide range of scenarios where they had used the skills. 65% of students used health action planning framework in their own personal self-care. Student nurses acknowledged barriers and enablers to their use of healthy conversation skills. Having knowledgeable mentors who role modelled healthy conversations skills in their consultations was the most frequently raised factor, in addition to lack of knowledge of local resources, time and confidence. All placement settings should ensure that registered nurses, especially those undertaking mentorship responsibilities have access to healthy conversation training.